2010
DOI: 10.1085/jgp.200910351
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic basis for LQT1 caused by S3 mutations in the KCNQ1 subunit of IKs

Abstract: Long QT interval syndrome (LQTS) type 1 (LQT1) has been reported to arise from mutations in the S3 domain of KCNQ1, but none of the seven S3 mutations in the literature have been characterized with respect to trafficking or biophysical deficiencies. Surface channel expression was studied using a proteinase K assay for KCNQ1 D202H/N, I204F/M, V205M, S209F, and V215M coexpressed with KCNE1 in mammalian cells. In each case, the majority of synthesized channel was found at the surface, but mutant IKs current densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…This result suggested that 0.46 pA is about the lower limit for the single-channel current at this potential. However, we felt that a much better way to show directly that the single-channel amplitude at full opening is ∼0.5 pA at +60 mV was to make single-channel recordings from a gating mutant of I Ks that we previously have shown (25) to have a much higher Po than WT channels. The whole-cell findings from the S209F mutant are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggested that 0.46 pA is about the lower limit for the single-channel current at this potential. However, we felt that a much better way to show directly that the single-channel amplitude at full opening is ∼0.5 pA at +60 mV was to make single-channel recordings from a gating mutant of I Ks that we previously have shown (25) to have a much higher Po than WT channels. The whole-cell findings from the S209F mutant are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The open dwell times were reduced to half that of WT ( Figure 4G and Table 1), consistent with the accelerated deactivation seen at the whole-cell level. 4 Closed dwell times ( Figure 4H) were best fit with 3 components, with only C f being different: 26.2 ms compared to 44.9 ms for WT (Table 1).…”
Section: I204fmentioning
confidence: 94%
“…4 The mutants D202H, I204F, and V205M all cause significant depolarizing shifts in the voltage dependence of opening (G-V) compared to WT ( Figures 1A and 1C). Each mutation has unique effects on channel kinetics: D202H causes very rapid deactivation, I204F causes particularly slow activation, and V205M causes both slowed activation and fast deactivation ( Figure 1B).…”
Section: Whole-cell Properties Of I Ks Lqts Mutantsmentioning
confidence: 94%
See 2 more Smart Citations